IMPLEMENTING THE MEANING OF HOSPITALITY AT PURA LUHUR BATUKAU TABANAN, BALI, THROUGH THE GO GREEN GO CLEAN COMMUNITY PARTNERSHIP PROGRAMME - Gede, Yoga Kharisma Pradana (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of writing this article is to make the community service of STPBI at Pura Luhur Batukau Tabanan a success, which is oriented towards expanding the benefits of tourism, especially in the study of hotel management science. In hotel management science, hospitality practices and cleanliness are factors that influence guest comfort. On the one hand, the environment of Pura Luhur Batukau looks less clean, and PKM Go Green Go Clean is carried out to reduce this comfort problem. The problems focus on: 1) What is the PKM Go Green, Go Clean at Pura Luhur Batukau Tabanan, Bali? 2) What is the meaning of hospitality in the PKM Go Green, Go Clean at Pura Luhur Batukau Tabanan, Bali?. This problem was solved using qualitative methods. All primary data was collected through interviews and participant observation in PKM Go Green, Go Clean activities. Meanwhile, secondary data was obtained based on a literature study. All data was analysed qualitatively using practice theory and reception theory. The research results show: 1) PKM Go Green Go Clean was carried out in the form of community service and providing hotel cleaning equipment at Pura Luhur Batukau Tabanan, Bali. This activity was held with the participation of PKM Go Green Go Clean partners and representatives of the STPBI academic community. 2) The meaning of hospitality is manifested in the form of expressions of friendliness and friendly service. The meaning of hospitality is implied in the cleaning activities and the rest activities at Pura Luhur Batukau.